2003
DOI: 10.1104/pp.103.029686
|View full text |Cite
|
Sign up to set email alerts
|

Light Control of Nuclear Gene mRNA Abundance and Translation in Tobacco

Abstract: Photosynthetic signals modulate expression of nuclear genes at the levels of mRNA transcription, mRNA stability, and translation. In transgenic tobacco (Nicotiana tabacum), the pea (Pisum sativum) Ferredoxin 1 (Fed-1) mRNA dissociates from polyribosomes and becomes destabilized when photosynthesis is inhibited by photosynthetic electron transport inhibitor 3-(3,4-dichlorophenyl)-1,1-dimethylurea. We used polymerase chain reaction suppressive-subtractive hybridization to identify similarly regulated endogenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 72 publications
1
29
0
Order By: Relevance
“…In addition to our observations of D1, we observed several other rapidly degraded proteins in our data set, with two of these proteins, THI1 and THIC, being involved in thiamine biosynthesis. In tobacco (Nicotiana tabacum), THI1 transcript abundance and polysome loading of this mRNA are high in the light and decrease in the dark (Tang et al, 2003), which would be consistent with our observations of the daily regeneration of THI1 protein. Recent work with the yeast THI1 ortholog THI4p reported that the sulfur atom necessary for thiazole synthesis was transferred from an internal Cys residue, leaving behind a dehydroAla residue so that this protein was classified as a suicide enzyme, due to the irreversible nature of this modification (Chatterjee et al, 2011).…”
Section: Reasons For Rapid Protein Degradationsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition to our observations of D1, we observed several other rapidly degraded proteins in our data set, with two of these proteins, THI1 and THIC, being involved in thiamine biosynthesis. In tobacco (Nicotiana tabacum), THI1 transcript abundance and polysome loading of this mRNA are high in the light and decrease in the dark (Tang et al, 2003), which would be consistent with our observations of the daily regeneration of THI1 protein. Recent work with the yeast THI1 ortholog THI4p reported that the sulfur atom necessary for thiazole synthesis was transferred from an internal Cys residue, leaving behind a dehydroAla residue so that this protein was classified as a suicide enzyme, due to the irreversible nature of this modification (Chatterjee et al, 2011).…”
Section: Reasons For Rapid Protein Degradationsupporting
confidence: 91%
“…Proteins from several other functional categories were also observed in the top 10, including an RNA-binding protein, a kinase, and a disulfide isomerase. Because the synthesis and turnover of several proteins on this list are known to be higher in the light (Tang et al, 2003;Pal et al, 2013), we were concerned that we were underestimating half-lives of this fastest set by considering data across all time points in our sampling regime, which encompassed long periods of darkness. To counteract this diurnal effect for the rapidly turning over subset, we also provide an estimate of the half-life for protein observations in the first 12-h time point, taking into account the lag in labeling time calculated from the average x intercept in the regression (Fig.…”
mentioning
confidence: 99%
“…Such a mechanism might act prior to, at, or after the import of the target proteins into the plastid. It has been shown that polyribosome binding, stability, and translation of transcripts of specific nuclear genes encoding photosynthesis-related proteins is dependent on plastid signals (Petracek et al, 1997;Sherameti et al, 2002;Tang et al, 2003). Plastid (redox) signals might also regulate the posttranslational import of proteins into chloroplasts (Jarvis and Robinson, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Some 59 UTR sequences are known to control translation (Kawaguchi and Bailey-Serres, 2002). Of particular interest, translation of both LHY (Kim et al, 2003) and many genes implicated in photosynthesis (Berry et al, 1988(Berry et al, , 1990Hansen et al, 2001;Tang et al, 2003) is light regulated. Although we cannot unequivocally conclude that translation of XCT message and degradation of XCT protein are light and clock regulated, these are interesting possibilities that merit further study.…”
Section: Xct Is Posttranscriptionally Regulatedmentioning
confidence: 99%